Comparison of relative uses of commercial assays for Toxoplasma gondii IgM antibodies. - Ashburn, D. (1992)
AIMS: To compare the sensitivity and user friendliness of seven commercially available enzyme linked immunoabsorbent assay (ELISA) kits for toxoplasma specific IgM. METHODS: Five antibody capture assays supplied by Abbott, Mercia, Northumbria, Organon and Sorin, and two indirect ELISA assays from Biostat and Mast, were assessed. Using defined dilutions of Toxoplasma gondii specific IgM, the performance and sensitivity of each assay was established. They were further assessed on a panel of 27 sera with a range of dye test and IgM results (as determined by the Scottish Toxoplasma Reference Laboratory). All of the assays were performed by three experienced operators and assessed for user satisfaction. RESULTS: The Mast, Organon, and Abbott assays were of low sensitivity; the Mercia and Northumbria were of high sensitivity; and the Biostat and Sorin assays produced too many false positive results. The Mercia kit provided most user satisfaction; the Mast and Abbott assays were most difficult to use. CONCLUSIONS: Local laboratories investigating toxoplasma infection should have three tests: one IgG and two IgM (high and low sensitivity) to help in the timing of infection. Alternatively, one sensitive IgM assay, such as that of Mercia, could be used by selecting appropriate high and low thresholds.